Transport policies in a two-sided market - Chiara Colesanti Senni; Noe Reidt (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
Decarbonizing the transport sector is a key measure to reduce carbon emissions at the global level. This result relies, among other factors, on the substitution of gasoline vehicles with electric vehicles. Countries such as Norway and Germany have adopted policies favoring the diffusion of electric vehicles. The success of such policies depends, however, on an adequate charging infrastructure. We therefore develop a two-sided market model that captures the network externalities between electric vehicles and charging stations. A platform provides, on one side of the market, electric and gasoline vehicles to consumers; on the other side, it supplies retailers with charging stations. This framework is used to study policies tackling different sides of the market. The main findings of the paper are: (1) policies targeting one side of the market generate feedback effects on the other; network externalities affect outcomes through their absolute size and relative intensity; (2) in the presence of network effects and environmental damage from polluting cars, policies can lead to a double dividend: decreasing the quantity of gasoline vehicles can be economically improving, while reducing the negative impact of pollution.
Keywords: H2; L22; L91; R40; 330; transport; two-sided markets; network effects; electric vehicles